The Role of Customer Engagement and Brand Trust in Mediating the Influence of Community Relationship Management and Marketing Orientation on Customer Loyalty at Bank raya Indonesia - Rachmawati, Shinta; Aditia Pratama, Yoga (Dinasti Publisher, 2025)
This study aims to analyze the factors influencing brand loyalty among customers of PT Bank Raya Indonesia Tbk, a digital bank undergoing strategic transformation amid intense competition in Indonesia’s digital banking industry. By adopting and testing the research model of Wongsansukcharoen (2022), this paper investigates the impact of Community Relationship Management (CoRM) and Relationship Marketing Orientation (RMO) on Brand Loyalty, with Customer Engagement (CE) and Brand Trust (BT) as mediating variables. A quantitative approach using a cross-sectional survey of Bank Raya customers was employed. Data will be analyzed using Structural Equation Modelling (SEM) to test the proposed hypotheses. The findings are expected to provide strategic input for Bank Raya in designing effective loyalty programs for its unique and dynamic market segments, while also contributing theoretically to marketing literature in the context of digital banking in developing countries.